Transmission line pulse (TLP) as integrative method for the investigation of ultra-fast trapping mechanisms on high-k MIM. (September 2019) - Merlo, L.; Rossetto, I.; Cerati, L.; Ghidini, G.; Milani, A.; Toia, F.; Piagge, R.; Di Biccari, L.; Gevinti, E.; Croce, G.; Andreini, A.
Abstract: This paper discusses the Transmission Line Pulse (TLP) analysis, generally used for electrostatic discharge (ESD) device characterization, as high potential usable tool also for non-ESD structures. TLP technique, combined with DC and pulsed I-V characterization, is performed to study the contribution of trap states on current conduction in Metal-Insulator-Metal (MIM) capacitors with an HfAlO stack. The importance of the above mentioned methods is demonstrated by comparing two generations of samples with slightly different charge trapping mechanisms; their impact on the current conduction is furthermore studied by decreasing the pulse width down to 50 nsec. TLP analysis is finally discussed as interesting method to investigate the influence of trap states on the device robustness. The evaluation of breakdown voltage for different time pulses allows to distinguish whether different failure mechanisms occur or not and to establish the impact of trap states. Ηighlights: TLP analysis is discussed as high potential usable tool for non-ESD structures. TLP, pulsed and DC analysis are used for characterization of trap states and current conduction in HfAlO high-k MIM. Current-voltage curves at different temperatures clarify nature of current conduction. Impact of trap states on current conduction is compared for different generations of samples and pulse widths down to 50 ns. TLP is used to investigate impact of trapping on robustness and possible presence of different failure mechanisms.